Harnessing friction stir back extrusion process to fabricate microtubes from as-cast Mg–4Zn–0.7Zr-1.6RE magnesium alloy. (1st March 2022) - Lakshminarayanan, A K; Ramachandran, Saranarayanan; Bakkiyaraj, M; Rajabharathi, B
Abstract: Friction Stir Back Extrusion (FSBE) is a novel manufacturing process widely used to produce lightweight tubes with superior mechanical properties. This work aims to establish the optimum process parameters of the FSBE method to fabricate flaw-free small-scale magnesium microtubes from as-cast Mg-Zn-Zr-Re magnesium alloy. FSBE experimental trials in the light of the Taguchi optimization were attempted to optimize and develop relationships that can link the crucial process parameters, namely tool rotational rate, feed rate, and billet preheating temperature of the FSBE process on the microstructural alterations, microhardness, and corrosion resistance characteristics. The results suggest that the FSBE parameters, especially the tool feed rate, have a crucial influence on the performance attributes of microtubes. Additionally, it is evident that both the tool rotation rate and feed rate significantly affect the formation of dynamically recrystallized fraction (DRX) of the stir zone. The stir zone has achieved a higher density of fine recrystallized grains than the base metal region, which subsequently led to a spike in the microhardness values of this zone. This study has determined that the FSBE technique significantly enhanced the corrosion degradation resistance of microtubes as compared with cast material. The optimal FSBE parameters such as tool rotational rate of 1440 rpm, feed rate of 20 mm min −1, and billet preheating temperature of 100 °C have offered microtubes with the highest microhardness and lowest corrosion degradation rate.